Risk factors for contamination of domestic hot water systems by legionellae. - Alary, M (1991)
To assess risk factors associated with the contamination of the domestic environment by legionellae, 211 houses in the Quebec City area were randomly selected and water samples were collected from the hot water tank, the shower heads, and the most frequently used faucet. After centrifugation, concentrated samples were seeded in triplicate on BCYE and GPV media. Data on the characteristics of the hot water system and plumbing in the house and on the personal habits of the occupants were collected for each house. Among these 211 houses, hot water was provided by either an oil or gas heater in 33 and by an electric heater in 178. Legionellae were isolated from none of the samples from houses with oil or gas heaters and from 39% (69 of 178) of those with electric water heaters (P less than 0.0001). This association remained highly significant after control for water temperature and other variables in a stratified analysis. In the 178 houses with an electric heater, 12% of the faucets, 15% of the shower heads, and 37% of the water heaters were contaminated. Legionella pneumophila serogroups 2 and 4 were the most frequently isolated strains. Logistic regression showed that factors associated with electric water heater contamination were (i) location of the house in older districts of the city (P less than 0.0001), (ii) old age of the water heater (P = 0.003), and (iii) low water temperature (P = 0.05). Contamination of the water heater was the only factor significantly associated with the contamination of peripheral outlets (P less than 0.0001).(ABSTRACT TRUNCATED AT 250 WORDS)